The first major vaccination campaign against smallpox in Lombardy: the mass vaccination campaign against coronavirus…nothing new…only terminology - Castaldi, SIlvana; Auxilia, Francesco; Piga, Maria Antonella; Gandolfi, Cecilia Eugenia; Franchini, Antonia Francesca; Porro, Alessandro; Galimberti, Paolo Maria (Acta Biomedica Atenei Parmensis, 2022)
Terminology, technology, communication and organizational strategies are different but we tried to compare the mass vaccination campaign against smallpox with the one we are doing against coronavirus.